Pull and Push Factors in Adventure Tourism - Ade Irma Anggraeni; Mukhamad Arfian Setyonugroho (Jurnal Akuntansi, Manajemen dan Ekonomi, 2021)
Indonesia is a country that has many volcanoes that are well-known among local and foreign tourists. This causes the mountain climbing Basecamp to pay more attention to their preparations in meeting the needs of tourists who come. Basecamp parties need to consider factors that can add value to the effectiveness and efficiency of mountain climbers who will carry out adventure activities on the mountain. Motivation, preparation, knowledge, and experience are the pull factors needed to influence the participation of mountain climbers to decide to climb the hill. In addition to considering the pull factors, the involvement of mountain climbers is also influenced by standard operational procedures, quality, security and cooperation with mountaineering basecamps with the other party is the driving factor.At the same time, the driving factor is self-motivation to carry out adventure tourism activities. Lifestyle, character, hobbies, or experience become a motivation to carry out this adventure tourism activity. For both beginner and experienced mountaineers, knowledge of mountaineering is essential to minimize risk and strengthen the determination to climb. Meanwhile, until now, research on push factors and pull factors is still very minimal. The research that will be carried out includes climbing Mount Slamet via Bambangan, which is the highest mountain in Central Java.